A difference in the composition of bronchial mucus between smokers and non-smokers. - Kollerstrom, N (1977)
The ratio of the amount of sulphated to sialic acid mucin (Su/Si) in the mucous glands of the human tracheobronchial tree has been investigated in seven smokers and seven non-smokers. The two mucins were studied in histological sections stained by the high iron diamine/Alcian blue pH 2-5 sequence and assessed by a point-counting method. Su/Si was greater in the smokers than in the non-smokers, who were almost completely distinguished by this ratio. A decrease in the ratio with each generation of branching from the trachea down the inferior lingular bronchial segmental pathway was seen in both the smoking and non-smoking groups. Analysis of the logarithm of Su/Si showed the smoking group means to be 2-3 times that of the non-smokers at each generation, and over both groups the average decrease down successive generations was given by a factor of 0-9.